Analysis of Wave Laboratory Reports to Identify Science Process Skills of UNNES Undergraduate Physics Education Students - Meutia, Eva; Supriyadi, Supriyadi; Wahyuni, Siti (Physics Communication, 2024)
The purpose of this study was to identify the science process skills of physics education students through analysis of practicum reports on wave courses at the Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang. The research method used is qualitative descriptive. The entire population in this study is used as a sample. Therefore, the sample in this study consists of third-semester students for the 2022/2023 academic year in the Physics Education program, totaling 94 students into 3 classes: A, B, and C. Observations indicate that the wave practical sessions are conducted using an open inquiry approach, without any practical guidance modules. The assessment of practical reports is conducted according to the predetermined evaluation rubric. The students' science process skills in preparing wave laboratory reports are categorized as high. Analysis results show that the highest average percentage of science process skills is found in the grouping indicator, at 88.32%, while the lowest is in the hypothesizing indicator, at 73.72%. The lecturer is assisted by laboratory assistants in evaluating the students' practical reports, with the assessment based on the results obtained in the report preparation. Students are considered to be in the high category if they are able to prepare reports according to the systematic report structure and meet the science process skills criteria.